Collagenous Tissues upon Lithium Treatment: A Quantitative Ultrastructural Study - Margaret Tzaphlidou (The Scientific World Journal)
In this review, the influence of lithium treatment in mouse, rat, and rabbit skin, liver, bone, and aorta, as well as arachnoid and dura mater collagen fibrils, is examined using electron microscopy and image processing. Structural changes (fibril architecture and diameter) are detected at the ultrastructural level in specimens from all lithium-treated tissues. The overall collagen fibril architecture is disturbed as compared with specimens from normal species. The mean diameter values of treated collagen fibrils are significantly smaller than those from controls in all tissues examined. The banding patterns of fibrils are normal in all cases. Measurements by a computerized method of measuring axial periodicity of fibrils indicate no effect of lithium on this parameter. Computer analysis shows no differences in charged amino acid composition between lithium-treated and -untreated samples. Under the present experimental conditions, lithium can induce permanent structural collagen alterations.